Characterization of Low‐Altitude Nightside Martian Magnetic Topology Using Electron Pitch Angle Distributions. Issue 10 (6th October 2017) - Weber, Tristan; Brain, David; Mitchell, David; Xu, Shaosui; Connerney, Jack; Halekas, Jasper
Abstract: Magnetic field lines at Mars act as direct pathways for both energy inflow and ion escape. Local variations in magnetic field topology can therefore directly impact the interaction between the solar wind and the Martian ionosphere. One method of analyzing magnetic topology is through the use of electron pitch angle distributions (PADs). Previous PAD investigations have characterized magnetic topology in the Martian system using data from the Mars Global Surveyor spacecraft, but these studies were orbitally constrained to ∼400 km altitude and 2 a.m./2 p.m. local time. With the Mars Atmosphere and Volatile Evolution (MAVEN) mission, we are now able to extend this analysis to a larger range of altitudes and local times. Here we use electron PADs measured using the Solar Wind Electrostatic Analyzer and Magnetometer instruments on MAVEN to analyze the magnetic topology of the nightside Martian environment. We use several characteristic PAD shapes to determine where Martian magnetic field lines are open or closed to the solar wind and present frequency maps of how these PAD shapes vary both geographically and with altitude. Finally, we present an initial analysis of the variation of the PAD shapes with local time, finding that trapped electron distributions become increasingly frequent as crustal fields rotate from dusk to dawn across the nightside of Mars. Key Points: Electron pitch angle distributions are used to determine magnetic topology at Mars Electron voids and trapped distributions indicate closed topology, found more frequently near crustal sources and at lower altitudes Trapped distributions become more frequent in crustal fields as they move from dusk to dawn across the nightside